studying the effect of fabrication technique of metal core on the Retention prosthesis (Journal of Hama University, 2024)
The success of prosthodontics depends on several things, the most important of which is the permanence of the compensation, which naturally depends on retention and resistance . And because metal-ceramic prostheses are still the most common and used prosthodontics in clinical terms, and due to the development of the techniques used in the manufacture of prosthodontics, it was necessary to test these new techniques to find out the real feasibility in testing stability.Comparison of the retention of a metal substructure using different fabrication techniques.A model was designed in the form of a tooth prepared for an upper first premolar with dimensions of 5 mm height and a chamfer finish line of 0.5 mm with occlusal wall convergence of 12 degrees. 30 main examples were manufactured by 3D printer and divided into 3 equal groups, then 10 metal core were manufactured by each method (traditional method, 3D printing method, milled wax lost wax) and cementation them by glass ionomer cement (VOCO-MERON). The test was carried out by a tensile strength measuring device located in the Industrial Research Center at the Ministry of Industry.The study showed that there are no statistically significant differences in the retention test between the manufacturing methods (traditional method, 3D printing method, milled wax lost wax) at the confidence level (0.05), and therefore any of the three methods can be used clinically.
Keywords: 3D printing technique(DLMS); Milled wax lost wax(mwlw); traditional technique; Retention prosthesis